Prisoners of Myth : the Leadership of the Tennessee Valley Authority, 1933-1990. - Hargrove, Erwin C. (Princeton University Press, 2001)
Prisoners of Myth is the first comprehensive history of the Tennessee Valley Authority from its creation to the present day. It is also a telling case study of organizational evolution and decline. Building on Philip Selznick's classic work TVA and the Grass Roots (1949), a seminal text in the theoretical study of bureaucracy, Erwin Hargrove analyzes the organizational culture of the TVA by looking at the actions of its leaders over six decades--from the heroic years of the New Deal and World War II through the postwar period of consolidation and growth to the time of troubles from 1970 onward.